Focusing on Good Responders to Pneumococcal Polysaccharide Vaccination in General Hospital Patients Suspected for Immunodeficiency. A Decision Tree Based on the 23-Valent Pneumococcal IgG Assay - Janssen, Lisanne M. A.; Heron, Michiel; Murk, Jean-Luc; Leenders, Alexander C. A. P.; Rijkers, Ger T.; de Vries, Esther (Frontiers in Immunology, 2019)
Background & Aim: Recently, the 23-valent IgG-assay was suggested as screening assay to identify poor responders to pneumococcal polysaccharide (PnPS)-vaccination with the serotype-specific assay as a second-line test. However, in a low pre-test probability general hospital setting predicting good responders could be more valuable to reduce the number of samples needing serotyping. Methods: Serotype-specific PnPS antibody-assays were performed for suspected immunodeficiency in two Dutch general hospitals (Jeroen Bosch Hospital, ‘s-Hertogenbosch; Elisabeth Tweesteden Hospital, Tilburg). 23-valent PnPS antibody-assays were subsequently performed in archived material. Data were analysed using receiver operating characteristic curves (AUC) and agreement indices (ICC). Results: Sera of 284 patients (348 samples) were included; 23-valent IgG-titres and the corresponding sum of PnPS-serotype specific antibodies showed moderate correlation (ICC=0.63). In 232 conjugated-pneumococcal-vaccine-naïve patients (270 samples), a random 23-valent IgG-titre could discriminate between samples with and without 7/11, ≥7/13 or  6/9 pneumococcal serotypes when both cut-off values 0.35 and 1.0 g/ml were used (AUC 0.86 and 0.92, respectively). All patients with a pre-immunisation-titre 38.2 g/ml and/or post-immunisation-titre 96.1 g/ml and none with a post-immunisation-titre 38.5 g/ml exhibited a good response to PnPS vaccination. Using these breakpoints as screening test to predict good responders, only 24% of patients would require further serotyping, as opposed to 68% if breakpoints to predict poor responders would have been used. Conclusion: In a low pre-test probability setting, the 23-valent IgG-assay proved to be a reliable screening test for good responders in conjugated-pneumococcal-vaccine-naïve patients, reducing the overall number of patient samples needing further serotyping, thus reducing overall costs of pneumococcal vaccination response assessment.